The influence of rhythmic and spectro-timbral musical features on gait-related movement - Johnson, Susan (2017)
Music makes us move, and humans have the universal tendency to synchronise their movements to music. This phenomenon has been used in music therapy to help people with movement disorders regain control over their movements. Rhythmic auditory stimulation has shown promising results in gait rehabilitation in various clinical populations. In healthy populations, various differences have been found between movement while walking to musical and metronome stimuli in terms of stride length. However, insufficient research has been conducted concerning the musical features that could evoke this difference, and which gait-related movements might change under the influence of music. The aim of this motion capture study was to investigate the effects of various rhythmic and spectro-timbral musical features on gait-related movement and to explore the differences between various types of auditory cues and their connections to movement. Participants were asked to walk to a variety of musical and metronome stimuli, which were divided into four tempo groups, ranging from 80 bpm to 145 bpm. Cadence and walking speed tended to increase with tempo, though exact period-matching of cadence to tempo generally did not occur. Furthermore, cadence and walking speed increased with the musical features pulse clarity and spectral flux. Participants also moved more smoothly to slower songs than to moderate tempo songs and fluidity of movement was negatively correlated with pulse clarity, low-frequency spectral flux, and mean spectral flux. Furthermore, stride length and walking speed were increased while listening to metronome beats compared to when listening to musical stimuli and participants tended to adapt their cadence more to the tempi of metronome stimuli than to musical stimuli. Also, musical timing affected hand distance, with decreased hand distance occurring in music with swung timing compared to music with straight timing. These results suggest that musical features can have a significant effect on gait-related movements in young healthy adults.